"Central Road" cystoscopic finding: The road to worsened incontinence following laparoscopic sacrocolpopexy. Issue 5 (1st July 2020) - Kato, Kumiko; Yoshimura, Yasukuni; Narushima, Masahiro; Suzuki, Shoji; Hattori, Ryohei
Abstract : Introduction: This paper presents the "Central Road" cystoscopic finding accompanied by magnified mixed urinary incontinence following laparoscopic sacrocolopopexy. Case presentation: A 70‐year‐old female experienced severe mixed urinary incontinence upon completing laparoscopic sacrocolopopexy. The cystoscopy showed a cord‐like appearance in the center of the bladder trigon and posterior wall. Videourodynamics confirmed stress urinary incontinence, and chain cystourethrography indicated that the proximal urethra was open and the posterior vesicourethral angle was atypically widened. After implanting a midurethral sling, mixed urinary incontinence was cured subjectively and objectively without medication. Conclusion: The "Central Road" cystoscopic finding can be a signpost pointing to laparoscopic sacrocolopopexy mesh overtensioning, which can cause dekinking of the bladder neck, exacerbate stress urinary incontinence, and possibly lead to stress‐induced instability. A midurethral sling successfully relieved mixed urinary incontinence in this case, but it might be necessary to loosen the laparoscopic sacrocolopopexy mesh in some other cases.